Initiation of bacteriophage lambda DNA replication in vitro with purified lambda replication proteins. - Wold, M S (1982)
We have developed a soluble enzyme system that replicates exogenously added plasmid DNA (lambda dv) bearing the replication origin of the bacteriophage lambda chromosome. The system contains pure phage lambda O and P replication proteins and a partially purified mixture of Escherichia coli replication proteins [the enzyme system of Fuller, R.S., Kaguni, J.M. & Kornberg, A. (1981) Proc. Natl. Acad. Sci. USA 78, 7370-7374). The features of lambda dv replication in this system closely resemble the known characteristics of phage lambda DNA replication in vivo. The system (i) depends completely on exogenously supplied DNA, (ii) specifically replicates supercoiled plasmid DNA that contains a lambda replication origin, (iii) depends on both the lambda O protein and the lambda P protein, (iv) depends on RNA polymerase, (v) depends on host replication proteins (e.g., primase, dnaB protein, and several others that function in the priming of DNA synthesis in E. coli) as judged by antibody inhibitions, and (vi) replicates as much as 32% of added lambda dv plasmid DNA through a single complete round to generate catenated daughter molecules. Furthermore, replication of lambda dv DNA in vitro requires DNA gyrase and an ATP-regenerating system. It is notable that addition of lambda O and P proteins to the mixture of E. coli replication proteins inhibits replication of plasmids bearing the origin of the E. coli chromosome. Exploitation of this enzyme system should allow a detailed investigation of the biochemical mechanisms involved in bacteriophage lambda DNA replication and its regulation.